Integration of Palliative Care into Primary Care: A Collaborative Effort Between the Indian Association of Palliative Care and the Indian Association of Preventive and Social Medicine - Shrikant Atreya; Savita Butola; Sushma Bhatnagar; Dinesh Kumar; Maryann Muckaden; Jyothsana Kuraikose; Jenifer Jeba; Mayank Gupta; Gayatri Palat; Pankaj Sanghai; Lulu Mathews; Gaurav Kumar; et al. (Indian Journal of Community Medicine)
India staggers at the 59th position (out of 81 countries globally) in the quality of death and dying index. A chronic life-threatening illness is often complicated by marginalized living, out-of-pocket health expenditure, illiteracy, and poor social support, and pushes the population further into the vicious spiral of suffering. The Indian Association of Palliative Care and the Indian Association of Preventive and Social Medicine joined hands in April 2023 to address the gap in the demand and availability of palliative care and proposed to empower Community Medicine physicians to provide primary palliative care. They put forth recommendations for education, service, and research developments in primary palliative care. In April 2023, the Indian Association of Palliative Care and the Indian Association of Preventive and Social Medicine joined hands to disseminate palliative care services to the community. Subsequently, a task force comprising faculties from Palliative Medicine and Community Medicine was formed. The position paper on primary palliative care jointly published by the Indian Association of Palliative Care and the Association of Family Physicians of India provided the framework for this position paper. The paper focused on education, service development, and research. The task force recommended the following: 1. Empower faculties and residents of the Department of Community Medicine, undergraduate students from medical and allied specialties posted to the department to provide primary palliative care. 2. Integrate palliative care into outpatient clinics (general OPDs in the hospital), community health centers, and home care as a part of the family adoption program. 3. Improve access to essential medications, including opioids, in urban and rural areas 4. Follow the recommendations of the National Health Policy 2017 to develop blended training programs for faculties and students. 5. Engage the community to identify patients with chronic life-threatening illnesses and allocate resources to support patients at home. 6. Collaborate to develop a protocol for regular audits and research for service improvisation.